Commitment of independent and institutional women directors to corporate social responsibility reporting. (29th November 2018) - Pucheta‐Martínez, María Consuelo; Bel‐Oms, Inmaculada; Olcina‐Sempere, Gustau
Abstract: This paper examines how independent and institutional women directors on boards affect corporate social responsibility (hereafter CSR) reporting. Most of the previous empirical evidence has shown a linear association between female directors and CSR disclosure, but to the best of our knowledge, no research has investigated the individual effect of independent and institutional female directors on CSR reporting. Therefore, the analysis of how the disclosure of CSR information is affected by independent and institutional women directors in a separate way merits our attention. Thus, we posit that there is a nonlinear association, concretely quadratic, between independent and institutional female directors on boards and CSR reporting. Our results demonstrate that, in line with the monitoring hypothesis, as the presence of independent and institutional women directors on boards increases, the CSR disclosure improves, but when their presence on boards reaches a tipping point (20.47% and 13.32%, respectively), CSR reporting decreases, which is consistent with the collusion hypothesis. This research contributes to the existing literature on the relationship between board gender diversity and CSR disclosure by suggesting that board structures formed by institutional and independent female directors have an effect on CSR reporting. Hence, female directors play a relevant role on boards since they may influence the CSR disclosure.